2004
DOI: 10.1080/00224490409552215
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and psychosexual development: Core gender identity, sexual orientation, and recalled childhood gender role behavior in women and men with congenital adrenal hyperplasia (CAH)

Abstract: Core gender identity, sexual orientation, and recalled childhood gender role behavior in women and men with congenital adrenal hyperplasia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
181
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(201 citation statements)
references
References 30 publications
14
181
0
6
Order By: Relevance
“…In contrast to the differences in interests, aspects of personality, spatial ability, and sexuality, gender identity is typical in the vast majority of CAH females [72,[77][78][79][80]. It is unclear what accounts for gender dysphoria in a small minority of females with CAH, but androgens appear not to play a significant role: there is not a relation between gender identity and indicators of prenatal androgen levels.…”
Section: Findings In Females With Cahmentioning
confidence: 83%
See 2 more Smart Citations
“…In contrast to the differences in interests, aspects of personality, spatial ability, and sexuality, gender identity is typical in the vast majority of CAH females [72,[77][78][79][80]. It is unclear what accounts for gender dysphoria in a small minority of females with CAH, but androgens appear not to play a significant role: there is not a relation between gender identity and indicators of prenatal androgen levels.…”
Section: Findings In Females With Cahmentioning
confidence: 83%
“…As a group, they are more likely to be sexually attracted to women than are their unaffected sisters [72,77]. Nevertheless, a majority of women with CAH report themselves to be exclusively heterosexual, and it is unclear what differentiates them from the approximately one-third who are bisexual or homosexual.…”
Section: Findings In Females With Cahmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, some studies reported a delay of sexual experiences, a reduced interest in sexual activities, lower maternalism, and a higher prevalence of bi-or homosexual orientation in women with CAH compared to the general female population [24,25,[121][122][123][124][125][126][127]. Moreover, it has been observed that girls with CAH who show the greatest alterations in childhood play behavior may be the most likely to develop a bisexual or homosexual orientation as adults [122] and that rates of bisexual and homosexual orientation were found to be correlated with the degree of prenatal androgenization [109] as well with genotype severity [128].…”
Section: XX Dsdmentioning
confidence: 99%
“…A combinação dessas alterações, que se manifestam desde o período intrauterino, é responsável pelo surgimento, ao nascimento, de um quadro clíni-co clássico na criança: genitália externa ambígua com vários graus de virilização (nas meninas) e macrogenitossomia (nos meninos), que podem ser acompanhadas por desidratação, arritmias cardíacas, choque e mesmo morte. Se o tratamento não for instituído precocemente, a exposição mantida ao excesso de andrógenos costuma resultar em manifestações adicionais, como aceleração da velocidade de crescimento, surgimento e crescimento de pelos no corpo (pubarca precoce), odor de padrão masculino, seborreia, acne, aumento da massa muscular e irritabilidade; com o tempo, poderão ocorrer alterações marcantes de tendência masculina (3)(4)(5)(6)(7)(8), inclusive comportamentais, motivos pelos quais o diagnóstico deve ser firmado precocemente e o tratamento, iniciado sem demora.…”
unclassified